Politics, Religion and Hate Speech in Zimbabwe. - Machingura, Francis; Sande, Nomatter (Oxford : Langaa RPCIG, 2023)
This book is empirically grounded on Zimbabwe and looks at hate speech as a bad omen for any society, family, nation and organisation. Hate speech divides and kills any peace, unity, tolerance, inclusivity, philosophy, race and geographical area, sacred places of worship, freedoms, identities, culture, unity and development in any space. It is not a good recipe for both animate and inanimate. It is never a solution to be applied in any geographical location. Hate speech, conflict and violence usually go together. The book clearly shows that, hate speech must never be tolerated in any religion, space (both private and public spaces), scriptures, society and nation. It is poisonous and manifests in different forms such as language (verbal or electronic), discriminations, beliefs, practices, laws, censorship, graffiti and even physical assault.
Abstract -- Introduction -- Conceptual Framework and Methodology -- Hate Speech in the Context of Disability -- Insights and Analysis into the Church's Interpretation of Biblical texts of disability -- The Impact of Hate Speech on the Actual Lived Experiences of Persons with Disabilities in Zimbabwe -- The Role of the Church in countering Disability Hate speech through fostering Positive Perspectives on Disability -- Conclusion -- References -- Chapter 7 -- Hate Speech as Index of the Heart in Zimbabwean Pentecostal Churches Leadership -- Abstract -- Introduction -- Theoretical Framework
Hate Speech and the Bible
eBooks on EBSCOhost
Keywords: Hate speech -- Zimbabwe; Zimbabwe -- Religion; Propagande haineuse -- Zimbabwe; Zimbabwe -- Religion; POLITICAL SCIENCE / World / African; Politics and government; Africa